Impact of Chemotherapy on Protein Levels in Cancer Patients Undergoing Treatment - Thakre Pratima (Multidisciplinary Journal of Akseprin Indonesia, 2025)
Cancer staging is a critical component of cancer management and directly influences the patient's treatment approach. Numerous protein tumor indicators assist in the diagnosis and prognosis of cancer patients. The objective of this study is to assess the total protein levels in serum samples from chosen cancer patients and to identify any correlations with various stages of the disease. Materials and Methods: Total proteins were quantified using the IR-VS spectroscopy approach and compared among various patients. Outcome: The spectrophotometric examination of the obtained serum samples indicated that chemotherapy-induced total protein loss correlates with the dysregulation of serum proteins and electrolytes. Total protein serves as a crucial indicator for assessing tumor stage in cancer patients; hence, it functions as a prognostic marker as well. It is a straightforward, non-invasive, and economical analytical approach